THE DIFFERENCE OF PREDICTED REFRACTION AND FINAL REFRACTION USING BARRETT II UNIVERSAL FORMULA AND SRK/T FORMULA IN HIGH MYOPIA PATIENTS AFTER PHACOEMULSIFICATION AND IOL IMPLANTATION AT DR. KARIADI GENERAL HOSPITAL SEMARANG - Irlinda, Riva; Astuti, Fatimah Dyah Nur (Majalah Oftalmologi Indonesia, 2023)
Introduction and Objective Studies have shown that 38% of refractive errors after intraocular lens (IOL) implantation are caused by deviations in calculation of IOL power using formulas. The difference between the formula’s refractive prediction and patient’s final outcome highly increases in cases of high myopia, but there needs to be more research on this topic. This study aims to show the difference between the predicted and final refractive outcomes using Barrett II Universal (BUII) formula and the SRK/T in patients with high myopia who underwent phacoemulsification and IOL implantation. Method This analytical observational study with cross-sectional design was conducted on patients with high myopia (axial length ? 26.0 mm) who underwent phacoemulsification and intraocular lens implantation between January 2021 and January 2022 at Dr. Kariadi General Hospital Semarang. The data used in this study consisted of biometric measurements and the difference between the predicted refractive outcomes using the BU-II and SRK/T formulas and the final refractive outcomes of patients one month after the surgery. The data were analyzed using a one-sample T-test, and significance level of p < 0.05 was considered statistically significant. Results Thirty-five eyes participated in this study, and the mean axial length was (29.33 2.01). The BU-II formula has a mean difference in the refraction prediction, with the patient's final refraction result being closer to zero (1.191.31) than the SRK/T formula (1.25 1,12). The refractive prediction difference between the two formulas was statistically significant (p < 0.05). Conclusion The BU-II formula has a lower difference between predicted refractive outcomes and final refractive outcomes of high myopia patients after phacoemulsification and IOL implantation than the SRK/T formula.